3′,4′-dihydroxyflavonol ameliorates endoplasmic reticulum stress-induced apoptosis and endothelial dysfunction in mice - Lau, Y.S.; Mustafa, Mohd Rais; Choy, K.W.; Chan, S.M.H.; Potocnik, S.; Herbert, T.P.; Woodman, O.L. (Nature Publishing Group, 2018)
Endoplasmic reticulum (ER) stress has been implicated in the development of hypertension 3 through the induction of endothelial impairment. As 3′,4′-dihydroxyflavonol (DiOHF) 4 reduces vascular injury caused by ischaemia/reperfusion or diabetes, and flavonols have been demonstrated to attenuate ER stress, we investigated whether DiOHF can protect mice from ER stress-induced endothelial dysfunction. Male C57BLK/6 J mice were injected with tunicamycin to induce ER stress in the presence or absence of either DiOHF or tauroursodeoxycholic acid (TUDCA), an inhibitor of ER stress. Tunicamycin elevated blood pressure and impaired endothelium-dependent relaxation. Moreover, in aortae there was evidence of ER stress, oxidative stress and reduced NO production. This was coincident with increased NOX2 expression and reduced phosphorylation of endothelial nitric oxide synthase (eNOS) on Ser1176. Importantly, the effects of tunicamycin were significantly ameliorated by DiOHF or TUDCA. DiOHF also inhibited tunicamycin-induced ER stress and apoptosis in cultured human endothelial cells (HUVEC). These results provide evidence that ER stress is likely an important initiator of endothelial dysfunction through the induction of oxidative stress and a reduction in NO synthesis and that DiOHF directly protects against ER stress- induced injury. DiOHF may be useful to prevent ER and oxidative stress to preserve endothelial function, for example in hypertension.